2006
DOI: 10.1111/j.1469-8137.2006.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

The mycorrhizal contribution to plant productivity, plant nutrition and soil structure in experimental grassland

Abstract: Summary• Previous studies have shown that arbuscular mycorrhizal fungi (AMF) can influence plant diversity and ecosystem productivity. However, little is known about the effects of AMF and different AMF taxa on other important community properties such as nutrient acquisition, plant survival and soil structure.• We established experimental grassland microcosms and tested the impact of AMF and of different AMF taxa on a number of grassland characteristics. We also tested whether plant species benefited from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
178
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 356 publications
(201 citation statements)
references
References 78 publications
(108 reference statements)
8
178
0
6
Order By: Relevance
“…Planting design was randomized 63 times and assigned to each microcosm. This approach was chosen to avoid potential differences among treatments being confounded by neighbourhood interactions and initial plant species composition (van der Heijden et al 2006). Seedlings that died within four weeks after planting were replaced so that each microcosm with sunflower and weeds contained 38 seedlings after 4 weeks.…”
Section: Experimental Model Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Planting design was randomized 63 times and assigned to each microcosm. This approach was chosen to avoid potential differences among treatments being confounded by neighbourhood interactions and initial plant species composition (van der Heijden et al 2006). Seedlings that died within four weeks after planting were replaced so that each microcosm with sunflower and weeds contained 38 seedlings after 4 weeks.…”
Section: Experimental Model Systemmentioning
confidence: 99%
“…Gerdemann & Trappe, isolate IMA1 from UK (AMF A), Glomus coronatum Giovannetti, isolate IMA3 (AMF B) and Glomus intraradices Schenck & Smith, isolate BEG 21 (AMF C). AMF A and B were obtained from pot-cultures maintained in the collection of the Department of Crop Plant Biology, University of Pisa, Italy and AMF C originated from Switzerland (see van der Heijden et al 2006 for a description). Inoculum of each isolate was propagated for approximately three months on Helianthus annuus in pots filled with a sterilized mixture of loamy soil and terra green (1:1).…”
Section: Fungal Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that AM fungal species are functionally distinct, in that some taxa provide disease resistance and others enhance nutrient supply to plants [13]. Furthermore, the diversity of AM fungi can potentially influence plant fitness, community structure, biodiversity, ecosystem productivity and variability [11,[13][14][15]. The beneficial effects of AM fungi on plant growth have led to the development of AM fungi as bioinoculants for forestry, agriculture and horticulture [16].…”
Section: Introductionmentioning
confidence: 99%
“…AM fungi play a key role in soil fertility, structure and ecology [10][11][12]. Recent studies have shown that AM fungal species are functionally distinct, in that some taxa provide disease resistance and others enhance nutrient supply to plants [13].…”
Section: Introductionmentioning
confidence: 99%